MUSIC THERAPY VERSUS DEEP BREATHING RELAXATION TO MANAGE STRESS IN CHILDREN WITH CANCER: AN INTEGRATIVE REVIEW - Amallia, Indah Reski; Allenidekania, Allenidekania (Jurnal Perawat Indonesia, 2021)
Introduction: Cancer can affect mental condition of children due to their chronic illness so that they can easily become stressed. Stress management with non-pharmacological methods is an independent intervention in nursing care. Music therapy and deep breathing relaxation were evidenced as effective to release stress of children with cancer. However, studies on comparing both methods have not been done. The purpose of this literature review is to compare the effectiveness of music therapy and deep breathing techniques to reduce stress experienced by children with cancer. Method: Research literature published from 2015 to 2020 and from the six largest databases: Springer Link, Science Direct, ProQuest, ClinicalKey, EBSCO, and PubMed using keywords (1) "music therapy OR music OR sing OR song" AND "stress OR distress OR anxiety" AND "pediatric oncology OR children oncology ”; (2) “relaxation OR deep breathing OR meditation OR yoga” AND “stress OR distress OR anxiety” AND “pediatric oncology OR children oncology”. Results: Eight articles were further analyzed with three themes found: 1) Supporting facilities; 2) Giving time; 3) Emotional support. Conclusion: This study strongly suggests that music therapy and deep breathing techniques should be considered as part of the holistic standard of pediatric oncology care. Non-pharmacological therapy can be more efficient if given in a timely manner.